Modeling and Simulation of Solid Oxide Fuel Cell Integrated with Anaerobic Digester, Thermal Storage Unit and Solar Collector: A Net Zero Emission System. (21st November 2022) - Naseer, Muhammad Nihal; Kamal, Khurram; Abid, Muhammad; Iqbal, Asif; Khan, Hamdullah; Zubair, Ch. Muhammad; Kumar, Sagar; Ratlamwala, Tahir Abdul Hussain; Muhammad Nauman, Malik
Abstract : Energy production from clean and green sources is one of the eminent challenges to mankind. Overall, all industrial sectors contribute to CO2 emission, but the energy production sector is a major contributor. In recent years, CO2 emissions from the energy sector have increased by 1.7%. Therefore, the development of alternative energy production sources is a pivot for researchers. In this regard, the fuel cell has been a promising technology but still accompanied by the release of greenhouse gasses but relatively lower than that of fossil fuels. The integration of the fuel cell to the biogas has been a promising factor to reduce emissions. This study contributes to the same by producing a self-sustaining biogas-fuel cell multigeneration system for cold areas. Mathematical modeling of all complements of the system, i.e., anaerobic digester, solid oxide fuel cell, solar collector, and thermal storage system, is provided. MATLAB/Simulink environment is used for simulation of the system. The proposed system will use an anaerobic digester for methane production. Hence, produced methane will be used to power solid oxide fuel cell. The electricity of the fuel cell will power the residential place, and the thermal potential of the exhaust will be stored. In daylight, the solar thermal potential will be utilized for district heating. In the absence of solar light, stored thermal energy will be used for district heating and hot water supply. Additionally, the CO2 emitted from the system will not be released into the environment but stored for industrial purposes. The best area of application of the proposed system is cold areas such as Switzerland.